Oral tradition revisited : a movie project / Sharina Saad ... [et al.] - Saad, Sharina; Sharulmizam, Sharifah Aina Shamira; Kamarul Ikhsan, Siti Nurul Aina; Ahmad Saifuddin, Rusdiana Puteri Ainaa Izzati (Universiti Teknologi MARA, Kedah, 2018)
The collection of stories and folklores of the Semai are disseminated through oral tradition practice. The language in a folktale is musical, rhythmic and melodic. In addition, the characters' direct dialogue punctuated with quick action excites readers' and listeners' interest. Despite these stories' age and genre, they still carry important messages to learners today. Frequently emphasized values for global citizenship, such as respect for diversity, human rights, and sustainable development, which the stories touch on, remain to be discovered and translated into daily life. Teachers can use this movie project for reading, writing and speaking skills activities. In addition, students craft a final performance to be shared with colleagues and teachers at the end of a class project. In this Ethnography research project, the author has gathered stories from the elderly Semai people through a snowball sampling technique. The stories were analysed to discover about the Semai beliefs and cultural heritage. The written stories have been adapted to animated movie by students for edutainment purposes. Students apply their language skills and use their creativity to produce the movies. The findings revealed that majority students preferred this edutainment project as it helps them comprehend the story better.